SPATIAL ECONOMETRIC ANALYSIS OF SOCIO-ECONOMIC DETERMINANTS OF MORTALITY IN POLISH SUB-REGIONS - Kujawska, Justyna; Reich, Magdalena (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
In Poland, in 2012 statistically at 1 000 inhabitants died 10 people, with at least 7 due to cardiovascular disease and cancer. In comparison with Western European countries, these values indicate poor health situation of Polish society. It can be assumed that responsible for the higher mortality rates in Poland are the stress caused by lack of work, the uncertainty of remuneration, the inactive lifestyle, unhealthy eating habits, overweight and obesity. The aim of this paper is to examine the significance of socio-economic determinants and their influence on deaths number in sub-regions in Poland in 2012. The method used is the linear econometric model with the spatial relationships. As a dependent variable the relative number of deaths in sub-regions in Poland per 1 000 inhabitants in 2012 is used. The results estimation indicate on the significant impact of education, unemployment and age on mortality in Poland and on the lack of influence of factors associated with affluence, such as the average gross wages and GDP per capita.